Kinetics of Cavitation of an Intermediate Fraction of Coal Tar - Balpanova, N.Zh.; Tusipkhan, A.; Gyul’maliev, A.M.; Ma, F.; Kyzkenova, A.Zh.; Aitbekova, D.E.; Khalikova, Z.S.; Baikenova, G.G.; Baikenov, M.I. (Solid Fuel Chemistry, 2020)
The kinetics of an intermediate fraction of coal tar with a boiling point of 230–300°C in the presence of a Fe3O4 nanocatalyst was studied. The rate constants of cavitation processing of coal tar were calculated using the Simpson method with a random search optimization, and the apparent activation energy of the cavitation process with the intermediate fraction of coal tar was determined. The effects of temperature, processing time, and the Fe3O4 nanocatalyst on the yield of polyaromatic hydrocarbons were shown.
Keywords: kinetics; coal tar; cavitation; nanocatalyst; rate constant